Analysis of the Effect of Exchange Rates, Inflation, Interest Rates, and Gross Domestic Product on the Balance of Trade in Indonesia - Raihan Febri Subiyanto; Raden Parianom (PT. Publikasiku Academic Solution, 2025)
The swift growth of economic relations between nations has led to greater participation in expanding trade flows, thereby fostering increased capital exchange among the countries involved. This study aims to analyze the effect of exchange rates, inflation, interest rates, and gross domestic product on Indonesia's trade balance from January 2014 to December 2023. The data used in this study are secondary data with monthly periods obtained from Badan Pusat Statistik (BPS), Bank Indonesia (BI), and the Ministry of Trade. The analysis method employed is the Error Correction Model (ECM), aimed at examining the short-term and long-term effects of the variables studied. The results indicate that, in the short term, the variables of exchange rate, inflation, interest rates, and gross domestic product have no significant effect on the trade balance. However, in the long term, the variables of inflation, interest rates, and gross domestic product have a significant effect on the trade balance, while the exchange rate variable has no significant effect on the trade balance in the long term.